HISTORY OF TRADITIONAL SINGING CULTURE - Kodirov D. K.; Abdug‘anieva G. M.; Nietbaeva X. A. (Bright Mind Publishing, 2025)
This article examines the history of traditional singing culture, its stages of development and specific features. Traditional singing is an integral part of the cultural heritage of the people, and it reflects the historical, social and cultural life of the Uzbek people. The article provides information about the main genres of traditional singing, the content and styles of songs, as well as the importance and development of traditional singing in modern times. Traditional singing culture is passed down from generation to generation as a powerful means of expressing the spirit and values of the people.
Keywords: Traditional singing, cultural history, Uzbek folk songs, song genres, cultural heritage, modern singing, folk music, folk traditions.